2013
DOI: 10.1101/gr.164749.113
|View full text |Cite
|
Sign up to set email alerts
|

A-to-I RNA editing occurs at over a hundred million genomic sites, located in a majority of human genes

Abstract: RNA molecules transmit the information encoded in the genome and generally reflect its content. Adenosine-to-inosine (A-to-I) RNA editing by ADAR proteins converts a genomically encoded adenosine into inosine. It is known that most RNA editing in human takes place in the primate-specific Alu sequences, but the extent of this phenomenon and its effect on transcriptome diversity are not yet clear. Here, we analyzed large-scale RNA-seq data and detected~1.6 million editing sites. As detection sensitivity increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
545
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 537 publications
(595 citation statements)
references
References 51 publications
22
545
0
Order By: Relevance
“…The vast majority of RNA editing sites detected here and in previous studies (Bazak et al 2014a;Picardi et al 2015) reside in Alu repetitive elements. To provide a more realistic estimate of global editing activity per cell, we calculated the Alu editing index (AEI) per cell because it represents the weighted average editing level across all expressed Alu sequences (PazYaacov et al 2015).…”
Section: Resultsmentioning
confidence: 51%
“…The vast majority of RNA editing sites detected here and in previous studies (Bazak et al 2014a;Picardi et al 2015) reside in Alu repetitive elements. To provide a more realistic estimate of global editing activity per cell, we calculated the Alu editing index (AEI) per cell because it represents the weighted average editing level across all expressed Alu sequences (PazYaacov et al 2015).…”
Section: Resultsmentioning
confidence: 51%
“…However, such highly specific A-to-I editing events within exonic ORF sequences are the exception in the context of present understanding. Of the several thousand A-to-I-editing sites identified through next generation sequencing studies, the vast majority is found within noncoding sequences of genes that are not inducible by IFN (56,(73)(74)(75)(76)(77)(78). What then is the molecular basis of the IFN-induced, dsRNA-dependent innate responses exemplified by eIF2␣ phosphorylation and SG formation that we now find are suppressed by A-to-I editing but are de-repressed in the absence of ADAR1 following IFN treatment?…”
Section: Discussionmentioning
confidence: 99%
“…A-to-I deamination has been observed at hundreds of thousands of sites and mostly occurs in non-coding and intronic regions, especially in targets containing Alu repeat sequences (8,9). When A-to-I editing occurs in coding regions, it has most commonly been associated with the recoding of brain proteins (10).…”
Section: C-to-u Rna Editing In Mammalsmentioning
confidence: 99%